Reducing schooling inequality in Brazil: Demographic opportunities and inter-cohort differentials - Carlos Eduardo Vélez; Sergei Soares; Marcelo Medeiros Coelho de Souza (Institute for Applied Economic Research (ipea), 2015)
The objective of this paper is to explore the interplay between schooling and demographics in Brazil. We would like to provide a preliminary answer to the question of how long will improvements in schooling of younger cohorts take o change the distribution of educational endowments of the total labor force. This answer depends on two factors. The first is the demographic composition of the working age population - the weight each cohort has in the 16 to 70 year old population. The second is the distribution of schooling within each cohort - its average educational level and the inequality within each cohort. These two factors - demography and education by cohort - define the average educational level and the distribution of education for the working age population in any given year. This paper takes a standard demographic projection and makes various hypotheses about the evolution of education - both the mean and inequality. According to these hypotheses, we will calculate how long improvements in the schooling of successive cohorts take to translate into significant improvements in the schooling of the working age population. Our results are somewhat pessimistic. We calculate that even very strong departures from the observed trend will take many years or decades to translate into significantly different educational endowments for the working age population. In other words, we show that demographic inertia is a strong factor preventing changes in educational endowments in periods shorter than a few decades.
Keywords: 330